2023
DOI: 10.1186/s12936-023-04699-9
|View full text |Cite
|
Sign up to set email alerts
|

Sterilized Anopheles funestus can autodisseminate sufficient pyriproxyfen to the breeding habitat under semi-field settings

Hamisi J. Kunambi,
Halfan Ngowo,
Ali Ali
et al.

Abstract: Background Anopheles funestus, the main malaria vector, prefer to oviposit in permanent and/or semi-permanent breeding habitats located far from human dwellings. Difficulties in identifying and accessing these habitats jeopardize the feasibility of conventional larviciding. In this way, a semi-field study was conducted to assess the potential of autodissemination of pyriproxyfen (PPF) by An. funestus for its control. Methods The study was conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Since there are many and diverse breeding habitats in rural areas, locating and treating them can present significant challenges. The efficacy of novel approaches like autodissemination of pyriproxyfen has been shown to be promising in addressing these situations [ 30 , 38 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Since there are many and diverse breeding habitats in rural areas, locating and treating them can present significant challenges. The efficacy of novel approaches like autodissemination of pyriproxyfen has been shown to be promising in addressing these situations [ 30 , 38 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Of importance, it has been demonstrated that sterilized mosquitoes can still transfer PPF sufficient to prevent adult emergence at the contaminated habitats 94 . This development, highlights the unique complementarity of autodissemination with bednets co-treated with pyriproxyfen.…”
Section: Potential Integration To Current Malaria Interventionsmentioning
confidence: 99%
“…The topical application of methoprene, another JHA, downregulated the expression of the ecdysone-regulated genes USP , HR3 , and Vg , which are involved in 20E action and oogenesis ( 20 ). Furthermore, exposure to PPF has been demonstrated to result in sterilization and fertility effects in adult male and female Anopheles arabiensis , Anopheles gambiae , Aedes aegypti , and Culex quinquefasciatus ( 12 , 21 24 ). In addition, exposure to non-lethal doses of PPF as larvae has been previously demonstrated to increase the susceptibility of Ae.…”
Section: Introductionmentioning
confidence: 99%